Risks of concealing environmental degradation - Matt W. Hayward; Kaya Klop‐Toker; Salim Momtaz; Eliza Payne; Louisa Rebec; Robert J. Scanlon; Craig M. Shuttleworth; Nick Valentine; Andrea S. Griffin (Conservation Biology, 2026)
Current practice seeks to conceal the visual impact of land‐use change (i.e., development). Six percent of development impact assessments in Australia and 14% of the World Bank's assessments recommend visual impact mitigation. This mitigation results in, for example, vegetated buffer strips alongside cleared agricultural areas and earthen mounds that block environmental degradation from view. These measures make living alongside such development more palatable, but they conceal its negative effects from the general public. The scale of the problem is global with evidence of mandated regulatory drivers for concealment from around the world. These mitigation measures limit the emotional impact of development on people, reducing their likelihood of implementing pro‐environmental actions. It is important for the populace to see the scale of human impacts on the environment to increase the likelihood of pro‐environmental behaviors and decisions that will help ease the crises facing the environment. We recommend overtly exposing the public to environmental degradation to improve understanding of environmental impacts, increase environmental knowledge, trigger pro‐environmental emotions and actions, and help recalibrate people's understanding of biodiversity loss. Policies and research into the effect of creative public imagery designed to improve communication into environmental destruction while minimizing habituation are important, and ensuring that the “greening” of gray infrastructure yields genuine biodiversity benefits is also critical.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Beyond species counts for assessing, valuing, and conserving biodiversity: response to Wallach et al. 2019 - Ninon F. V. Meyer; Niko Balkenhol; Trishna Dutta; Maarten Hofman; Jean‐Yves Meyer; Euan G. Ritchie; Charlotte Alley; Chad Beranek; Cassandra K. Bugir; Alex Callen; Simon Clulow; Michael V. Cove; et al. (Conservation Biology, 2021)
Article impact statement : Combining native and non‐native species to evaluate biodiversity is overly simplistic and may undermine the conservation of ecosystems.

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.